Covalent Organic Framework (COF)‐Based Hybrids for Electrocatalysis: Recent Advances and Perspectives. Issue 12 (27th October 2021) - Tang, Jiayi; Su, Chao; Shao, Zongping
Abstract: Developing highly efficient electrocatalysts for renewable energy conversion and environment purification has long been a research priority in the past 15 years. Covalent organic frameworks (COFs) have emerged as a burgeoning family of organic materials internally connected by covalent bonds and have been explored as promising candidates in electrocatalysis. The reticular geometry of COFs can provide an excellent platform for precise incorporation of the active sites in the framework, and the fine‐tuning hierarchical porous architectures can enable efficient accessibility of the active sites and mass transportation. Considerable advances are made in rational design and controllable fabrication of COF‐based organic–inorganic hybrids, that containing organic frameworks and inorganic electroactive species to induce novel physicochemical properties, and take advantage of the synergistic effect for targeted electrocatalysis with the hybrid system. Branches of COF‐based hybrids containing a diversity form of metals, metal compounds, as well as metal‐free carbons have come to the fore as highly promising electrocatalysts. This review aims to provide a systematic and profound understanding of the design principles behind the COF‐based hybrids for electrocatalysis applications. Particularly, the structure–activity relationship and the synergistic effects in the COF‐based hybrid systems are discussed to shed some light on the future design of next‐generation electrocatalysts. Abstract : A graphic illustration of well‐designed covalent organic framework (COF)‐based hybrid systems containing a COF organic skeleton and inorganic electrocatalytic active species. The synergistic effects brought by the combination of COFs with other inorganic species, including metallic or carbon components, would endow the system with high activity, conductivity, and durability. Sometimes multifunctionalities can also be achieved with the hybrid electrocatalysts.